Assessing The Effectiveness of The PNP Internal Disciplinary Mechanism in Enhancing Job Satisfaction among Personnel - Fisher, Marilou M.; Madolid, Jeannette C.; Demate, Erlan M.; Corsena, Ardie R.; Villa, Elizabeth; Mobo, Froilan D.; Golla, Nathaniel S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The study aimed to improve the job satisfaction among PNP person-nel by addressing the issues in the PNP's internal disciplinary mech-anisms. The Dasmarinas Component City Police Station PCOs and PNCOs took part in the study, descriptive comparison research de-sign was used to examine the internal cleansing and disciplinary mechanism programs applied. The data was collected using a sur-vey questionnaire that was consistent with PNP Memorandum Cir-culars 2019-027 and 20-2020. Kusumawardani (2024) asserted that work discipline increases job satisfaction. If job satisfaction de-creases, so does work discipline. This was achievable because em-ployees were satisfied with their jobs, enjoy fair working hours, and follow their superiors' and subordinates' rules. The majority of the respondents were PNCO, consisting of male participants whom were all college graduates. The research showed that the internal disciplinary procedures of the Dasmarinas Component City Police Station, particularly those related to punitive measures, had resulted in an increase in job satisfaction. It highlighted the importance of reaffirming the fundamental principles of the Philippine National Police (PNP) Maka-Diyos, Makabansa, Makatao, and Makakalikasan while also promoting the ethical standards of a public official. The PIAS concluded that errors resulted from the examined variables.